Screening and stability analysis of groundnut (Arachis hypogaea) for resistance to early leaf-spot (Cercospora arachidicola) - Chandra, Satish; Sharma, B K; Singh, J; Pandey, D K (The Indian Journal of Agricultural Sciences, 2012)
An experiment was conducted during the rainy season of 1991-93 to evaluate 25 geneotypes of groundnut (Arachis hypogaea L.) for their resistance and stability to disease reaction of early leaf-spot (Cercospora arachidicola Hori.) at Barapani. Â . Disease severity was moderate in 1991 and 1992, whereas it was high in 1993 causing heavy defoliation in the susceptible control (’ JL 24 ’). All the genotypes showed less early leaf-spot scored compared with the control, indicaling satisfactory level of resistance. Significant genotype X nlvironment (G X E) interaction was observed for disease reaction. Both linear and non linear components of GxE Â interaction were significant. Genotypes ’ICGV 86020’, ’ICGV 86680’ and ’ICGV 87350’ were found stable and promising Â for low-disease reaction in different years.